Pharmacovigilance Program impact on notifications of adverse reactions to antineoplastic drug in a university hospital - Carlos Alberto WAYHS; Tatiana Von DIEMEN (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To evaluate the Pharmacovigilance Program impact on notifications of adverse reactions to antineoplastic drugs (ADR) in a university hospital. Methods: Cross-sectional, descriptive and retrospective study, carried out by surveying spontaneous notifications of suspected antineoplastic ADR arising from hospitalization and chemotherapy outpatient clinics and sent to the Pharmacovigilance Program of the Clinical Pharmacy section, of the Pharmacy Service of a university hospital in Porto Alegre. This work was approved by the Research Ethics Committee of that institution under number 2019-0408. Results: In 2020, the Pharmacovigilance Program received 71 notifications involving antineoplastic ADR, representing 59.7% of the total notifications received. In 2021, ADR notifications involving antineoplastics represented 47% (n=49) of notifications received. In 2022, the notifications received had an even greater reduction, with 24, representing 37% of the total notifications received in the year. In the year 2023, however, it was possible to observe an increase both in the number of spontaneous reports suspected of total ADR (n=95), as well as in the number of antineoplastics (n=45) and, consequently, in the percentage of spontaneous reports suspected of ADRs. antineoplastic ADR (47%). Conclusion: The notifications monitoring involving antineoplastics by Pharmacovigilance demonstrated the need to formulate a strategy to return to the notifier with educational objectives in conjunction with professionals from the chemotherapy outpatient clinic and the care area involved in the notifications.